PERBEDAAN HASIL PEMERIKSAAN RETIKULOSIT SEBELUM DAN SESUDAH AKTIVITAS FISIK - Dewi Hartati; Indah Sari; Zahra Tulhaya Jannah (IKesT Muhammadiyah Palembang, 2023)
Introduction: Reticulocytes are young blood cells that have just been released into the bloodstream from the bone marrow. Reticulocytes have characteristics that still have ribosomal RNA remnants. Physical activity is a body movement produced by skeletal muscles and requires energy, including activities performed while working, playing, doing household chores, exercising, and traveling.. Purpose: The purpose of this study was to determine the differences in the results of reticulocyte examination before and after physical activity. Research Method: This research was conducted in 2 laboratories, blood sampling at the Hematology Laboratory, Faculty of Science and Technology, Muhammadiyah Palembang Institute of Health Sciences and Technology, and at the Palembang Health Laboratory Center. The number of samples used was 17 with 2 treatments using purposive sampling technique. Based on the results of reticulocyte examination before and after physical activity using the sysmex-XN1000 hematology analyzer. Results: The results showed that before physical activity produced an average of 1.24% while those after physical activity produced an average of 1.12%. In this study, there was a decrease that was not far from its normal value. Analysis of the data using the Wilcoxon test results obtained sig 0.209 where p≥0.05. Conclusion: The conclusion of this study is that there is no difference between before and after physical activity.